Post sunset equatorial spread-F at Kwajalein and interplanetary magnetic field. Issue 8 (15th October 2017) - Rastogi, R.G.; Chandra, H.; Janardhan, P.; Reinisch, B.W.; Bisoi, Susanta Kumar
Abstract: We connect the time sequence of changes in the IMF-Bz to the development of spread-F at an equatorial station Kwajalein on three different nights in November 2004, one during a geomagnetic quiet period and other two during geomagnetic disturbed periods. The chosen days show clear and smooth variations of IMF-Bz without any large fluctuations thereby enabling one to correlate changes in equatorial spread-F with corresponding changes in IMF-Bz. It is shown that a slow and continuous increase in the IMF-Bz over a duration of few hours has a similar effect on the equatorial ionosphere as of a sudden northward turning of the IMF-Bz in causing an electric field through the polar region and then to the equator. We conclude that the Spread-F at equatorial and low latitudes are due to echoes from ionization irregularities that arise due to the plasma instabilities generated by an eastward electric field on the large plasma density gradient in or below the base of the F-layer during any period of the night time along with the gravity driven Rayleigh-Taylor instability.